Nurses' Work Motivation Influences Handwashing Compliance Before and After Five Moments at A General Hospital in Banjarmasin - Noor Amaliah; Amalia Salsabila; Dewi Kartika Wulandari; Muthmainnah Muthmainnah (Universitas Malahayati Lampung, 2026)
ABSTRACT Healthcare-associated infections (HAIs) are a major concern, often linked to healthcare workers' hand hygiene. Adherence to